Treatment options for pericoronitis in dental practice - Adrienn Beszedics; Szilvia Koncz; Norbert Cziriák; Gábor Kammerhofer; Sándor Bogdán; Zsolt Németh (Hungarian Dental Association, 2024)
Pericoronitis is an intraoral soft tissue infection most commonly associated with impacted teeth. The most frequently impacted teeth are lower third molars. Definitive treatment of the disease usually involves removing the affected tooth. Pericoronitis can be exacerbated by local and systemic conditions. This publication describes pericoronitis, its aetiology, clinical manifestation and treatment options.